Particle motion in a space-time of a 3D Einstein gravity with torsion - Kaya, R.; Ozcelik, H. T. (SPRINGER/PLENUM PUBLISHERS, 2021)
We analyze the motion of both massive and massless particles in a model with space-time of 3D Einstein gravity with torsion. We consider the spinor field and the massless scalar field as the source of torsion respectively. Following the Hamilton-Jacobi formalism, we investigate the effective potential of radial motion for test particles in a homogeneous and isotropic space-time with torsion. We show that there are no stable circular orbits for massive and massless particles in the Einstein gravity with torsion induced by the spinor field, in a space-time with two spatial and one time dimensions. In the case of massive particles, we show that stable orbits exist in 3D Einstein gravity with torsion induced by the scalar field.
Keywords: Particle motion; Torsion; Spinor field; Scalar field; BLACK-HOLE; CHARGED-PARTICLES; TRAJECTORIES; SPIN; Astronomy & Astrophysics; Physics